Targeted LOWering of Central Blood Pressure in patients with hypertension: Baseline recruitment, rationale and design of a randomized controlled trial (The LOW CBP study) - Sharman, J.; Stanton, T.; Reid, Christopher; Keech, A.; Roberts-Thomson, P.; Stewart, S.; Greenough, R.; Stowasser, M.; Abhayaratna, W. (2017)
Background: High blood pressure (BP) is the most common modifiable cause of death from cardiovascular disease. Lowering BP with medication improves patient outcomes, but even in populations with normal upper arm (brachial) BP there remains considerable residual risk for cardiovascular disease and this may be due to persistently elevated central BP. There has never been a trial to determine the value of targeted central BP lowering among patients with hypertension, and this was the aim of this study. Methods: This is a multi-centre, randomized, open-label, blinded endpoint trial among 308 patients treated for uncomplicated hypertension with controlled brachial BP (< 140/90 mmHg) but elevated central BP (≥ 0.5SD above age- and sex-specific normal values). Baseline recruitment has been completed. Participants were randomized to intervention with spironolactone (25 mg/d) or usual care and are being followed over 24 months, with the primary outcome being left ventricular mass index (using cardiac magnetic resonance imaging). Brachial and central BP will be measured in the clinic, at home over 7-days and by 24-h ambulatory monitoring. Aortic stiffness will be assessed by carotid-to-femoral pulse wave velocity. Primary (intention to treat) analysis will determine the role of central versus brachial BP for predicting changes in left ventricular mass index. Conclusions: Compared with control, intervention is expected to significantly lower left ventricular mass index, and this effect is expected to be independently correlated with central BP lowering. These findings would support the concept of central BP as an important therapeutic target in hypertension management. Results are expected in 2018.